The mitochondrial genome data of the Capsicum annuum cv. Dempsey (Solanaceae)NCBI - Seona Yun; Junseong Bae; Jeongbin Park; Hyeran Kim (Data in Brief)
Capsicum annuum L. (1753), commonly known as pepper, holds significant economic value as one of the globally cultivated horticultural crops. This study presents the mitochondrial genome of the sweet pepper C. annuum cv. Dempsey, assembled using Illumina NovaSeq data. The circular mitogenome is 577,453 base pairs (bp) in length and includes 36 protein-coding genes, three ribosomal RNA genes, and 43 transfer RNA genes. Phylogenetic analysis reveals that C. annuum is not monophyletic, with C. annuum cv. Dempsey identified as a sister to the hot pepper C. annuum cv. Jeju. This study provides as a valuable resource for comparative analyses of pepper mitogenomes, enhancing our understanding of the evolution and adaptive mechanisms of pepper species.